2023
DOI: 10.1002/we.2855
|View full text |Cite
|
Sign up to set email alerts
|

The flow in the induction and entrance regions of lab‐scale wind farms

Abstract: With the increasing demand for wind energy, it is important to be able to understand and predict the available wind resources. To that end, the present wind tunnel study addresses the flow in the induction and entrance region of wind farms through particle image velocimetry, with focus on differences between actuator disks and two‐bladed rotating wind turbine models. Both staggered and aligned farm layouts are examined for three different incoming wind directions. For each layout, 69 disks or turbines are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…The highest demand and largest source of renewable energy in the global market is currently onshore and offshore wind [99]. Wind energy is based on the conversion of kinetic energy into rotational energy, which is then converted into electrical energy by means of a shaft [100].…”
Section: Onshore and Off-shore Renewable Energymentioning
confidence: 99%
“…The highest demand and largest source of renewable energy in the global market is currently onshore and offshore wind [99]. Wind energy is based on the conversion of kinetic energy into rotational energy, which is then converted into electrical energy by means of a shaft [100].…”
Section: Onshore and Off-shore Renewable Energymentioning
confidence: 99%
“…This is usually experienced as a decrease in the approaching wind speed due to the presence of the wind farm, resulting into a reduction of the Annual Energy Production (AEP) of the farm under consideration. Early wind-tunnel studies 1,2,3 and numerical simulations 1,4,5,6 confirmed that the presence of wind turbines is perceived by the approaching wind that, consequently, tries to avoid the farm by deflecting upward or on the sides, decreasing the intensity of the wind that enters the wind farm and that can be exploited to produce power. The industrial wind community needed a tool to assess this loss and a number of theoretical corrections were proposed 7,8 to assess wind-farm blockage for generic layouts: some of these methods have become standard assessment tools implemented in wind analysis software.…”
Section: Introductionmentioning
confidence: 97%